Effect of respiration dynamics on postural control following a 5k run - Harper, E.; Strang, A.; Walsh, M.; Caserta, B.; Haworth, J.; Hieronymus, M. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Research has shown postural control during upright stance can be diminished for up to twenty minutes following aerobic exercise of different types, intensities, and durations (Lepers et al., 1997; Nagy et al., 2002). Researchers have posited that this is caused by neuromuscular changes associated with aerobic exercise and fatigue such as the reduced excitability and central drive to peripheral muscles (Lepers et al., 2002), vestibular desensitization (Lepers et al., 1997), and peripheral somatosensory desensitization (Lepers et al., 1997). However, no research has measured or attempted to control for the influence that changes in respiration dynamics (e.g., rate and volume) alone might have on postural sway. The aim of the current study was to examine these effects in order decipher whether changes to postural control following intense aerobic exercise (a 5-kilometer run performed with maximal effort) can be attributed to effects of exercise and fatigue or simply changes in respiration.